Evaluation of Restaurants and Restaurant Experiences - General Weightings and Individual Deviations in the Underlying Evaluation Criteria: Results of a Survey in Switzerland and Germany - Michael Beier (ZBW - Leibniz Information Centre for Economics, 2025)
It is especially important for restaurants to understand exactly who their potential and actual guests are and what exactly those guests expect from a restaurant or a restaurant visit. In particular, it is of interest to know which criteria potential guests use to select restaurants and under which circumstances guests are satisfied with their restaurant visit. A great deal of research has already been conducted internationally on such evaluation criteria. However, no comparative findings are yet available for Switzerland and Germany. Against this background, this research report presents answers to various questions on evaluation criteria for restaurants on the basis of newly collected data. At the same time, diners need to know who can give them good recommendations or inspire them to try new restaurants that match their own preferences and expectations. The same applies to restaurants and industry-related online platforms, information services, and social online networks that need to understand exactly how restaurant recommendations can best be conveyed. Against this background, this research report is also interested in the question of how people differ in terms of their evaluation criteria for restaurants and how these differences might affect the fit of restaurant recommendations and satisfaction with such recommendations. For the research described in this report, 1,004 German-speaking people in Switzerland and Germany were surveyed using an online questionnaire. Among other questions, respondents were presented with a catalogue of 33 different evaluation criteria, for each of which they were asked to indicate how important these criteria were to them in relation to restaurants and their own restaurant experiences.
Keywords: 330; Restaurants; Gastronomy; Evaluation criteria; Customer experience; Recommendations; Word of mouth